"I've always lived in a place with gardens": Residents' homemaking experiences in Australian aged-care gardens. (January 2020) - Tsai, Mimi; Cushing, Debra Flanders; Brough, Mark
Abstract: Gardens play a vital role in homemaking for many older people living in aged-care facilities. A garden is where residents can assert ownership, agency, and recall significant memories, especially after relocation in later life. This research addresses a gap in literature about aged-care gardens by expanding notions of therapeutic benefits. It adopts a phenomenological framework and applies unstructured interviews, Go-Along videorecording and digital storytelling for data collection. Findings suggest residents are not merely passive users of gardens, they are active creators, shaping their outdoor environment through gardening and creating meanings in their local landscape that contribute to their experience of being 'home'. Highlights: Gardens reinforce the concept of 'home' and reinterpret feelings of home in Australian aged-care facilities. Residents engage with homemaking to transform their roles from passive receivers to active contributors in the garden. Aged-care gardens blur the boundaries between communal and private spaces. A healthful landscape experience integrates aged-care residents' emotional, social and sensory landscape experiences.